Pengolahan Limbah Organik Pasar Sayur Kota Metro Sebagai Media Kultur Maggot Hermetia Illucens Melalui Pot Biokonversi Bagi Peternak Ayam Skala UMKM - Muhammad Saidun Anwar; Yuning Eka Rahma Wati (Universitas Nurul Jadid, 2024)
This activity aims to explore the effectiveness of applying organic waste from the Vegetable Market in Metro City as a medium for Hermetia Illucens maggot culture, as well as to determine the ecological and economic impacts of the activity on small-scale poultry farmers in Metro City. The community service was conducted using the Asset Based Community Development (ABCD) method. Several points were obtained from the conducted community service: first, the discovery and dream phase involved educating and socializing the potential of organic waste as a maggot cultivation asset, as well as formulating the desired targets. Second, the design and define phase aimed to formulate program activities to achieve the targets, including determining the timing, location, and necessary equipment. Third, the destiny phase included the implementation of the community service, which involved education and practical activities such as hatching maggot eggs, making larva maggot breeding boxes, sorting and fermenting organic waste, and constructing a production house. Based on the monitoring conducted, challenges were found in the form of predator attacks such as rats, chickens, and green flies on the maggot egg hatching containers. Evaluation was carried out by creating special containers equipped with lamp lighting and using netting as covers for the containers. Challenges were also found in the aspect of maggot growth, where the utilization of organic waste from the Metro City vegetable market was not sufficient to maximize growth. Therefore, evaluation was conducted by mixing organic waste from the Metro City vegetable market with household waste generated by each partner of the community service. Education and mentoring in the management of organic waste from the Metro City vegetable market have impacted the community's perspective on viewing organic waste as a valuable asset and their skills in managing waste as a medium for maggot cultivation.